The Optimism and Problem-Focused Coping in Students Who Work Part-Time in the City of Kupang - Polin, Megaliana Bramiyanti; Lerik, Mariana Dinah Ch; Benu, Juliana Marlin Y (Universitas Nusa Cendana, 2023)
Students who work part-time have greater demands than ordinary students. Many demands make students feel depressed and stressed so they need to do coping. Good problem-focused coping will emerge if students have optimism. The purpose of this study was to determine the relationship between optimism and problem-focused coping among students who work part-time. The type of research used in this research is a quantitative approach with correlation analysis. The sample used was 110 students who work part time in Kupang City. The data collection method used the optimism scale and problem-focused coping scale and was analyzed using the Pearson product- moment correlation. The results showed that there was a significant positive relationship between optimism and problem-focused coping. This relationship is indicated by the calculated r value of 0.852 > r table of 0.186 and the significance value is 0.000.